A Phi-Class Glutathione S-Transferase Gene for Verticillium Wilt Resistance in Gossypium arboreum Identified in a Genome-Wide Association Study. (20th November 2017) - Gong, Qian; Yang, Zhaoen; Chen, Eryong; Sun, Gaofei; He, Shoupu; Butt, Hamama Islam; Zhang, Chaojun; Zhang, Xueyan; Yang, Zuoren; Du, Xiongming; Li, Fuguang
Abstract: Verticillium wilt disease is one of the most destructive biotic stresses faced by cotton plants. Here, we performed a genome-wide association study (GWAS) in 215 Chinese Gossypium arboreum accessions inoculated as seedlings with Verticillium dahliae to identify candidate loci involved in wilt resistance. We identified 309 loci that had a significant association with Verticillium wilt resistance and - log( P ) values >5.0; the highest signal appeared on Ca3 in a 74 kb haplotype block. Five genes were also located within this haplotype block. One of these genes, CG05, was positioned close to the most significant SNP Ca3_23037225 (14 kb); expression of the gene was induced by V. dahliae or by treatment with salicylic acid (SA). Therefore, we suggest that CG05 may respond to invasion by V. dahliae via an SA-related signaling pathway, and we designated this gene as GaGSTF9 . We showed that GaGSTF9 was a positive regulator of Verticillium wilt through the use of virus-induced gene silencing (VIGS) and overexpression in Arabidopsis. In addition, the glutathione S -transferase (GST) mutant gstf9 of Arabidopsis was found to be more susceptible to Verticillium wilt than wild-type plants. The levels of endogenous SA and hydrogen peroxide had a significant effect on Arabidopsis plants that overexpressed GaGSTF9, indicating that GST may regulate reactive oxygen species content via catalytic reduction of the tripeptide glutathione (GSH), and then affect SA content. Our data demonstrated that GaGSTF9 was a key regulator mediating cotton responses to V. dahliae and a potential candidate gene for cotton genetic improvement.